2007
DOI: 10.1093/beheco/arm035
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of urban red foxes (Vulpes vulpes) reduce the risk of traffic-induced mortality

Abstract: Traffic collisions can be a major source of mortality in wild populations, and animals may be expected to exhibit behavioral mechanisms that reduce the risk associated with crossing roads. Animals living in urban areas in particular have to negotiate very dense road networks, often with high levels of traffic flow. We examined traffic-related mortality of red foxes (Vulpes vulpes) in the city of Bristol, UK, and the extent to which roads affected fox activity by comparing real and randomly generated patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 52 publications
4
65
0
Order By: Relevance
“…Similarly, mortality of Badger Meles meles was higher on minor roads than on major roads (van Langevelde et al 2009). Behavioural adaptation found in several mammals, like change in home range, movements and diurnal activity patterns, as well as escape response to vehicle traffic, can result in reduced number of roadkills (Trombulak & Frissell 2000, Seiler & Helldin 2006, Baker et al 2007). A conceptual model showing a curved (parabolic) relationship between traffic density and number of roadkill is earlier presented based on empirical data on moose-vehicle collisions (Seiler & Helldin 2006), but as far as I know this is the first time for birds.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mortality of Badger Meles meles was higher on minor roads than on major roads (van Langevelde et al 2009). Behavioural adaptation found in several mammals, like change in home range, movements and diurnal activity patterns, as well as escape response to vehicle traffic, can result in reduced number of roadkills (Trombulak & Frissell 2000, Seiler & Helldin 2006, Baker et al 2007). A conceptual model showing a curved (parabolic) relationship between traffic density and number of roadkill is earlier presented based on empirical data on moose-vehicle collisions (Seiler & Helldin 2006), but as far as I know this is the first time for birds.…”
Section: Discussionmentioning
confidence: 99%
“…There are several hypotheses that could explain this finding: 1) a gradual decline of the species abundance in the region due to previous high mortality rates (Eberhardt et al, 2013); 2) a restriction of species movements by reducing the attempts of road crossings due to a higher perception of risk (e.g. Baker et al, 2007); and/or 3) an overall reduction in habitat quality (McClure et al, 2013) due to increasing traffic noise. Patterns of road-kills, increasing or stable over seven years, do not support the interpretation of population depletion due to road-kill (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both the red fox and rabbit are species with clear anti-predatory behaviours, which may make them more alert to changes in traffic intensity and therefore avoid those with heavy traffic. The historical human persecution towards foxes may lead them to be cautious, reducing the rate at which they cross roads when traffic is higher (Baker et al, 2007). In an experimental study, rabbits showed that at the presence of a predator, they increase avoidance and vigilance while feeding (Monclús et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations